Reasons that influence the choice of an University in secondary students of the Region San Martin - Tarrillo, José (2016)
The aim of this study was to identify the reasons that influence the choice of an University in secondary students of the Region San Martin. The study sample consisted of 1528 secondary students, both sexes between 14 and 19 years. A questionnaire that measures the reasons for choosing a univer-sity was built. Academic level, prices of Carreras, physical location Campus, Student Environment and Labor Conventions: The following reasons were taken into account. The psychometric properties show that it is valid and reliable. Among the main findings it was found that 72.2% of secondary school, choose a university for the academic level, 11.2% for labor agree-ments and 7.7% for the prices of degrees.